Future perspectives on novel CAR-T therapeutics beyond CD19 and BCMA in onco-hematology - Ershova, Alina; Goldaeva, Alexandra; Staliarova, Alena; Bulatov, Emil; Petukhov, Alexey; Barlev, Nikolai (Frontiers in Immunology, 2025)
CAR-T cell therapy is a type of adoptive immune therapy that relies on the specific targeting of cytotoxic T-cells to eliminate the malfunctioning cells in the body. Genetic engineering allows the generation of an almost infinite variety of chimeric antigen receptors (CAR) to ensure specificity for antigens on the surface of target cells. Therefore, CAR-T appears to be a powerful and versatile therapy for the treatment of various diseases, including cancer. Recently, CAR-T has emerged as a significant advancement in the management of hematological tumors, particularly B-cell malignancies, mainly due to the presence of specific antigens such as CD19 and BCMA. As a result, the market for CAR-T therapy is experiencing significant growth. However, the problem of relapses remains and warrants the search for new therapeutic approaches, including CAR-T technology. In this case, one of the major challenges is finding and evaluating new targets for CAR-T in terms of their likelihood of success. Here we propose a set of established criteria for the evaluation of potential targets for CAR-T cell therapy to treat hematological malignancies. These criteria include assessing the target in terms of its biological characteristics, such as expression level, cellular localization, tissue specificity, and clinical aspects, including unmet clinical needs and the success of clinical trials. Using these criteria, we validate our prediction of the next CAR-T cell therapy targets that will likely emerge soon.